Melatih Keterampilan Berpikir Kritis Pada Topik Larutan Penyangga Melalui Pengembangan E-Modul Berbasis Pendekatan Saintifik - Hidayati, Ririn Eva; Khoiroh, Naimatul (Balai Diklat Keagamaan Bandung, 2024)
This study was undertaken to develop an e-Module based on a scientific method that can teach critical thinking skills on the issue of buffer solutions that are legitimate, practical, and successful. This development research employs a 4-D methodology (Define, Design, Develop, and Disseminate). Validity, practicality, and efficacy are the three limits assessed. Data is analyzed using quantitative descriptive approaches. The E-Module produced has a validity of 3.31 with extremely valid criteria, a practicality of 90%, an effectiveness of 83.33%, an N-gain score of 0.69, an average completion of 83.33%, and an 88% response rate from students. The E-Module is acceptable for class XI due to its validity, practicality, and efficacy. The e-modules that have been created can supplement existing instructional resources at madrasas. Keywords: critical thinking skills; e-module; scientific approach; buffer solution